Reactive amine surfaces for biosensor applications, prepared by plasma-enhanced chemical vapour modification of polyolefin materials - Volcke, C.; Gandhiraman, R.; Gubala, V.; Raj, J.; Cummins, T.; Fonder, G.; Nooney, R.; Mekhalif, Z.; Herzog, G.; Daniels, S.; Arrigan, Damien; Cafolla, A.; et al. (Elsevier, 2010)
Here we have demonstrated a solventless plasma-based process that integrates low-cost, high throughput,high reproducibility and ecofriendly process for the functionalization of the next-generationpoint-of-care device platforms. Amine functionalities were deposited by plasma-enhanced chemicalvapour deposition (PECVD) using a new precursor. The influence of the plasma RF power and the deposition time on surfacial properties, as well as their effect on the reactivity and content of amino groups was investigated. The key process determinants were to have a sufficient power in the plasma to activate and partially fragment the monomer but not too much as to lose the reactive amine functionality, and sufficient deposition time to develop a reactive layer but not to consume or erode the amine reactivity. An immunoassay performed using human immunoglobulin (IgG) as a model analyte showed an improvement of the detection limit by two orders of magnitude beyond that obtained using devices activated by liquid-phase reaction.